Does trade openness contribute to driving financing flows for development? - Jean-François Brun; Sèna Kimm Gnangnon (World Trade Organization (WTO), 2017)
Trade has been recognized in the 2030 development Agenda as well as in the Addis Ababa Agenda for Action as an important means for the implementation of the Sustainable Development Goals (SDGs). This paper questions whether trade openness could be an important driver of financing for development flows, notably development aid (ODA), Foreign Direct Investment (FDI) inflows, and government public revenue, the latter being the ultimate financing source for development for any country. The paper also takes advantage of the framework of analysis to investigate the interplay between these three types of financial flows. Relying on an unbalanced panel dataset comprising 125 countries, of which 37 are Least Developed Countries (LDCs), the empirical analysis uses the three stage least squares econometric approach and provides two important pieces of evidence: first, international trade openness is an important tool for driving financial flows for development, including government public revenue, development aid and FDI. As a result, it could contribute to mobilizing the substantial financial resources needed for development, including for the implementation of the SDGs. Second, there are strong interactions (complementarity and substitutability) between these three types of financing for development flows.
Keywords: F13; F30; P33; O11; 330; Trade Openness; Government public revenue; ODA inflows; FDI Inflows